"Impact of Sub-Lethal Monosodium Glutamate Exposure on Hepatic Protein Profiles in Labeo Rohita" (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluated the ecotoxicological impact of Monosodium Glutamate (MSG) on the freshwater fish Labeo rohita (Rohu). The experiment focused on alterations in liver total protein levels following chronic sub-lethal exposure. Labeo rohita were exposed to a constant sub-lethal dose of 10 mg/L of MSG across three progressive temporal intervals: 5, 10, and 15 days. A parallel control group was maintained in chemical-free freshwater. Quantitative estimation of total liver proteins was conducted using standard spectrophotometric methods.The results demonstrated a highly significant, time-dependent decline in total liver protein concentration in all MSG-exposed groups compared to the control group. The baseline liver protein level in the control group was recorded at 65.4 ± 1.2 mg/g of wet tissue. Upon exposure to 10 mg/L of MSG, liver protein levels dropped to 52.1 ± 1.0 mg/g on Day 5, 41.8 ± 0.9 mg/g on Day 10, and reached a minimum value of 28.5 ± 0.7 mg/g on Day 15. This marked depletion highlights severe physiological stress, metabolic reallocation, and potential cellular degradation in the hepatic tissue. The study confirms that even low concentrations of agricultural or industrial MSG runoff pose a threat to aquatic organisms by disrupting essential protein synthesis pathways.